Liprin-α-Mediated Assemblies and Their Roles in Synapse Formation - Xie, Xingqiao; Liang, Mingfu; Yu, Cong; Wei, Zhiyi (Frontiers in Cell and Developmental Biology, 2021)
Brain’s functions, such as memory and learning, rely on synapses that are highly specialized cellular junctions connecting neurons. Functional synapses orchestrate the assembly of ion channels, receptors, enzymes and scaffold proteins in both pre- and post-synapse. Liprin-α proteins are master scaffolds in synapses and coordinate various synaptic proteins to assemble large protein complexes. The functions of liprin-αs in synapse formation have been largely uncovered by genetic studies in diverse model systems. Recently, emerging structural and biochemical studies on liprin-α proteins and their binding partners begin to unveil the molecular basis of the synaptic assembly. This review summarizes the recent structural findings on liprin-αs, proposes the assembly mechanism of liprin-α-mediated complexes, and discusses the liprin-α-organized assemblies in the regulation of synapse formation and function.